Technology and Power. A Foucauldian Analysis of Electronic Monitoring Discourses - Vitores, Anna; Domènech, Miquel (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2007)
The article aims to show the importance of FOUCAULT within social studies of science and technology. It also illustrates how a Foucauldian analysis can be useful for studies of science, technology and society focused on power effects. To accomplish these objectives we analyze the emergence of a specific techno-scientific innovation: the electronic monitoring of offenders. We map the discontinuities and discourse dispersions linked to those practices that constitute different materializations of this electronic device. Because we start from questions concerning power technologies, rather than simply analyzing the ideologies and knowledges that legitimate electronic monitoring and its technical reliability, we attend to the assemblage of discourses, rhetorics, vocabularies, techniques and procedures by which knowledge is intertwined and joins with the exercise of power. In this way, we show how one of FOUCAULT's technologies of power—disciplinary technology—is articulated, nourished and contradicted by other emergent logics drawing on new forms of regulation and social control.URN: urn:nbn:de:0114-fqs070225